2014
DOI: 10.2134/jeq2013.10.0402
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Leaching in Californian Rice Fields: A Field- and Regional-Scale Assessment

Abstract: Irrigated croplands can be a major source of nitrate-N (NO-N) in groundwater due to leaching. In California, where high NO-N levels have been found in some areas of the Central Valley aquifer, the contribution from rice systems has not been determined. Nitrate leaching from rice systems was evaluated from soil cores (0-2 m), from the fate of N fertilizer in replicated microplots, and from about 145 regional groundwater wells. Soil NO-N concentrations were ≤3.3 mg kg (usually <1 mg kg) below the root zone (belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…This was attributed to denitrification during the rice growing season when fields are flooded, ammonia volatilization, plant uptake, and crop management practices that contribute to the development of a hardpan layer directly below the rice root zone. The study also found very low nitrate concentrations in groundwater wells near rice fields (median value less than 1 mg L −1 NO 3 -N) (Liang et al, 2014) consistent with our estimates of Rice nitrogen loading. The GNLM mass balance estimates are outside the range of our model-predicted CIs for Rice as they reflect nitrogen losses prior to denitrification or ammonium volatilization potentially taking place in saturated clay soils of rice fields.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This was attributed to denitrification during the rice growing season when fields are flooded, ammonia volatilization, plant uptake, and crop management practices that contribute to the development of a hardpan layer directly below the rice root zone. The study also found very low nitrate concentrations in groundwater wells near rice fields (median value less than 1 mg L −1 NO 3 -N) (Liang et al, 2014) consistent with our estimates of Rice nitrogen loading. The GNLM mass balance estimates are outside the range of our model-predicted CIs for Rice as they reflect nitrogen losses prior to denitrification or ammonium volatilization potentially taking place in saturated clay soils of rice fields.…”
Section: Discussionsupporting
confidence: 89%
“…Credibility intervals of posterior probability densities of estimated nitrogen loading rates for selected crop groups plotted with historical field measurements of nitrogen loading from California (Devitt et al, 1976;Embleton et al, 1979;Letey et al, 1977;Pratt et al, 1972;Pratt and Adriano, 1973;Adriano et al, 1972;Allaire-Leung et al, 2001;Liang et al, 2014). Thinner lines are 95 % credibility intervals, thicker lines are 68 % credibility intervals, the solid dot is the median estimated value, and the open black circles are historical field measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Denitrification in the root zone and deeper in the soil profile explains the small amount of nitrate leached to the groundwater under rice fields in clayey soils in California, USA (Liang et al, 2014). Shallow groundwater (< 1.5 m) under cultivated vertisols (e.g., the Netherlands) showed large variability (spatial and temporal) in nitrate concentration, probably due to the highly variable oxygen concentrations and therefore variability in nitrogen transformations in these systems (Hendriks et al, 1999).…”
Section: Kurtzman Et Al: Soil-aquifer Phenomena Under Vertisolsmentioning
confidence: 99%